Pemberdayaan Masyarakat Melalui Pengembangan Desa Wisata di Desa Sukawening - Dyah Istiyanti (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
The project aims to examine the ongoing process of community empowerment through the development of a tourism village including the form of community empowerment and the results of community empowerment carried out. The approach used in this study includes a qualitative method for assessing community characteristics and village government policies. Data collection was obtained through interviews and observations. The observations stated that several activities in the village could support the development of a tourist village in Sukawening Village, including rabbit farming, edamame cultivation, sandals, and cultural activities managed by the Sarapala team. Forms of community empowerment involve community participation starting from planning and implementing activities. The programs that have been carried out in the form of socialization of the development of tourism villages include socialization on marketing, water and health, inventory of village potentials in the framework of village spatial planning, and training in making biodiesel and soap from used cooking oil. Community empowerment through the development of a tourism village has implications for regional cultural resilience in the form of cultural strengthening, especially archery and some changes in social and environmental values.